The (un)importance of school assignment - Nadine Ketel; Hessel Oosterbeek; Sándor Sóvágó; Bas van der Klaauw (Tinbergen Institute, 2023)
We combine data from the Amsterdam secondary-school match with register data and survey data to estimate the effects of not being assigned to one's first-ranked school on academic outcomes and on a wide range of other outcomes. For identification we use that secondaryschool assignment in Amsterdam is based on the deferred acceptance mechanism with ties broken by lottery numbers. Losing the admission lottery for one's first-ranked school affects the characteristics of the assigned school, the home-school distance and the characteristics of teachers and peers. Despite the different school environment, we find no negative effects on academic outcomes, nor on any other outcome, including: time on homework, help with homework, attitudes towards school, awareness of parents, behavior inside school, behavior outside school, school satisfaction, civic engagement, having friends, and students' personality. It seems therefore that the concerns that parents of lottery losers express about their children's school assignment are based on the characteristics of schools, teachers and peers and not on academic or non-academic outcomes.
Keywords: I21; I24; C26; 330; Schulauswahl; Bildungsverhalten; Bildungsniveau; Zufriedenheit; Verhalten; Schüler; Niederlande